Influence of Concentrated Power Endurace Workloads on Sprinters' Functional State - Rita Sadzevičienė; Viktoras Šilinskas; Jonas Poderys (Lithuanian Sports University, 2018)
Research  background  and  hypothesis. There  are  few  studies  about  the  variables  of  the  duration  of  power- endurance workloads and their total and residual effects. Research aim was to evaluate the changes in the functional state indices of muscular and cardiovascular systems while two training micro-cycles were designed to develop power-endurance abilities, and the third one was appointed for active rest. Research methods: Seven sprint athletes performed two micro-cycles of concentrated power-endurance type loads  and  one  micro-cycle  was  appointed  for  recovery. Three  groups  of  indices  were  chosen:  muscular  power; cardiovascular indices and indices of recovery. 12-leads ECG was registered during the Ruffier test and 30 s vertical jumping tests. Research  results.  Under  the  influence  of  two  training  micro-cycles  using  concentrated  power  endurance workloads muscular power deteriorated and the recovery rate was individual. After two training micro-cycles the effect  of  total  fatigue  caused  an  increased  biological efforts  to  perform  the  locomotion task  and  cardiovascular changes were more expressed than before training. Seven days was a too short period of time so that the changes in the indices caused by total effect of training would return to the baseline values again. Discussion  and  conclusions.  Reduced  abilities  in  the  regulation  of  peripheral  vascular  tone  after  heavy training could be compensated by the changes in the cardiac function, i. e. by an increase in systolic blood pressure. Cardiovascular indices could be useful for describing changes in the functional state of athletes under the influence of training. Keywords: cardiovascular system, recovery, anaerobic load.